Pancasila and The Construction of The Legal Hierarchy in Indonesia - Abunawas Had; Muh. Arif Maulana; Masdianawati Masdianawati (Al-'Adl, 2022)
This paper aims to provide a general description of the existence of Pancasila philosophy in the hierarchy of laws in Indonesia. Pancasila's initial position as a grand norm to the end of Pancasila's role in the course of law in Indonesia. The research method used in this study is a normative research method by collecting data from the library and various literature and from the internet, which is the primary data material and secondary data material based on predetermined qualifications. The finding showcased two things: First, Pancasila's philosophical understanding is based on the positivistic values of Hans Kelsen that the law has levels (stufenbau theory) that must be objective without prejudice and justice. Second, Pancasila should be used as the primary basis in the formation of law in Indonesia to produce laws that follow the values of Pancasila.